2002
DOI: 10.1128/aac.46.9.2926-2932.2002
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Genotypic and Pharmacokinetic Determinants of the Virological Response to Lopinavir-Ritonavir-Containing Therapy in Protease Inhibitor-Experienced Patients

Abstract: The response to regimens including lopinavir-ritonavir (LPV/r) in patients who have received multiple protease (PR) inhibitors (PI) can be analyzed in terms of human immunodeficiency virus type 1 (HIV-1) genotypic and pharmacokinetic (pK) determinants. We studied these factors and the evolution of HIV-1 resistance in response to LPV/r in a prospective study of patients receiving LPV/r under a temporary authorization in Bordeaux, France. HIV-1 PR and reverse transcriptase sequences were determined at baseline L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
3
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 12 publications
7
72
3
1
Order By: Relevance
“…This efficacy of lopinavir-ritonavir in protease inhibitor experienced patients was observed previously in clinical trials or in other expanded access datasets and in the whole cohort of 792 patients (8,13) In the current retrospective analysis, we demonstrated that inhibitory quotient evaluated using genotypic test results was a better predictor of the virologic response than virological (genotype) or pharmacological (C min ) approaches used separately, especially among patients with at least 3 protease inhibitor resistance mutations. The observation of predictivity of the GIQ, even among patients with substantially reduced genotypic susceptibility to lopinavir-ritonavir, is in accordance with its pharmacokinetic profile, in which mean trough levels (5,500 ng/ml) are sustained far above (Ͼ75-fold when dosed at 400/ 100 mg twice-daily) the human serum-adjusted 50% inhibitory concentration for wild-type virus (inhibitory quotient Ͼ 75).…”
Section: Discussionsupporting
confidence: 55%
“…This efficacy of lopinavir-ritonavir in protease inhibitor experienced patients was observed previously in clinical trials or in other expanded access datasets and in the whole cohort of 792 patients (8,13) In the current retrospective analysis, we demonstrated that inhibitory quotient evaluated using genotypic test results was a better predictor of the virologic response than virological (genotype) or pharmacological (C min ) approaches used separately, especially among patients with at least 3 protease inhibitor resistance mutations. The observation of predictivity of the GIQ, even among patients with substantially reduced genotypic susceptibility to lopinavir-ritonavir, is in accordance with its pharmacokinetic profile, in which mean trough levels (5,500 ng/ml) are sustained far above (Ͼ75-fold when dosed at 400/ 100 mg twice-daily) the human serum-adjusted 50% inhibitory concentration for wild-type virus (inhibitory quotient Ͼ 75).…”
Section: Discussionsupporting
confidence: 55%
“…Interestingly, this effect was not observed when clone C5 was tested, implicating an association of the I93L mutation with this phenotype. It is notable that this mutation was previously reported to be associated with isolates from patients who had failed lopinavir therapy in clinical trials in which individuals infected with subtype B were studied (14). We could not observe any difference in the IC 50 s of the other commercially available PIs tested when the IC 50 s for these two clones were compared to those for strain HXB2/NL4-3-PR.…”
Section: Discussionmentioning
confidence: 56%
“…The present results provide insight into exploratory algorithms for LPV resistance, shown in Table 4, which are based either on the correlation of genotype and phenotype in the isolates from PI-experienced patients (22,31,40) or the correlation of baseline genotype with virologic response in PIexperienced patients (17). In general, these algorithms have been shown to be predictive of the virologic response to LPV-RTV therapy in PI-experienced patients (8,17,21,25,35). All of the canonical PI mutations (15) emerging upon rebound in PI-experienced subjects in this study are contained in at least one algorithm, including L10I, K20M/R, L24I, L33F, M46I/L, G48V, I54V, and V82A, which appear in three or more of the four algorithms (Table 4).…”
Section: Discussionmentioning
confidence: 99%